METAPHOR IN NIGHTWISH`S DARK PASSION PLAY ALBUM - Jaka Sampoerna; Sortha Silitonga (LINGUISTICA, 2014)
ABSTRACT This research focuses on metaphor used in Nightwish`s Dark Passion Play album. The research was conducted by using descriptive qualitative method. The data are collected from the song lyrics in Nightwish`s Dark Passion Play album. The findings of the study show that there are 83 occurrences of eight types of metaphor. They are active metaphor (8), inactive metaphor (3), subjective metaphor (3), mimetic metaphor (17), phenomenalistic metaphor (4), precision metaphor (7), symbolism metaphor (18), and approximate metaphor (23). The most dominant type used in Nightwish`s Dark Passion Play album is approximate metaphor (27,71%). It means that the point of this album is a description of the idealism of the band about life. Approximate metaphor is a kind metaphor that has no clear ground and topic, it create smany interpretations from reader and hearer and made this album never stopped being discussed. Keyword: Metaphor, Lyric, Song.